Comparison of Leukocyte-Rich Platelet-Rich Plasma and Leukocyte-Poor Platelet-Rich Plasma on Achilles Tendinopathy at an Early Stage in a Rabbit Model. Issue 5 (April 2020) - Jiang, Guangyao; Wu, Yifan; Meng, Jiahong; Wu, Fengfeng; Li, Sihao; Lin, Mu; Gao, Xin; Hong, Jianqiao; Chen, Weishan; Yan, Shigui; Yan, Ruijian; Feng, Gang; et al.
Background: Tendinopathy is still a great challenge in clinical practice, and the role of platelet-rich plasma (PRP) is controversial. The influence of leukocytes on tendinopathy at an early stage has not been defined so far. Purpose: To compare the effects of leukocyte-rich PRP (Lr-PRP) and leukocyte-poor PRP (Lp-PRP) on Achilles tendinopathy when applied at an early stage. Study Design: Controlled laboratory study. Methods: A rabbit Achilles tendinopathy model was induced by a collagenase injection. A week later, treatments were applied randomly on local Achilles tendon lesions: (1) 200 μL of Lr-PRP (16 legs), (2) 200 μL of Lp-PRP (16 legs), and (3) 200 μL of saline (16 legs). At 3 and 6 weeks after the collagenase injection, outcomes were evaluated by histology, magnetic resonance imaging (MRI), real-time polymerase chain reaction analysis, immunohistochemistry, and transmission electron microscopy (TEM). Results: The Lr-PRP group had a lower T2 signal intensity ( P = .0377) and smaller diameter ( P = .0193) and cross-sectional area ( P = .0194) than the Lp-PRP group on MRI. Histologically, the Lr-PRP group had better scores than the Lp-PRP group ( P = .0284 and P = .0188, respectively). Compared with the Lp-PRP group, higher gene expression and more protein synthesis of collagen I ( P = .0160 and P = .0309, respectively) and CD163 ( P < .0001 and P = .0411, respectively) were found in the Lr-PRP group. Considering TEM and biomechanical testing, the Lr-PRP group demonstrated more mature collagen fibers ( P < .0001), a larger fiber diameter ( P = .0005), a higher failure load ( P = .00417), and higher tensile stress ( P < .0001) than the Lp-PRP group. Conclusion: Lr-PRP had more beneficial effects than Lp-PRP when delivered at an early stage during tendon repair. Clinical Relevance: Here, we showed that tendinopathy influenced the curative effects of PRP in vivo. An early-stage application of Lr-PRP had more benefits for the repair of tendinopathy than Lp-PRP in a rabbit model, which will supplement guidelines of PRP treatment on tendinopathy clinically.